A sketch of Arnfried Antonius (1934 - 2010) - Steiner, Sascha CC (Universidad de Costa Rica, 2012)
Arnfried Antonius studied Zoology, Paleontology and Ethnology at the University of Vienna, Austria, gradually focusing his attention on the ecology and graphic microanatomical reconstructions of marine invertebrates